Tropics of savagery : the culture of Japanese empire in comparative frame - Tierney, Robert Thomas, 1953- (Asia Pacific modern ;, 2010)
This is an incisive and provocative study of the figures and tropes of 'savagery' in Japanese colonial culture. The author demonstrates how imperial Japan constructed its own identity in relation both to the West and to the people it colonized.